Moderate Prenatal Alcohol Exposure Impairs Performance by Adult Male Rats in an Object-Place Paired-Associate Task - Sanchez, Lilliana M. (Behav Brain Res, 2018)
Memory impairments, including spatial and object processing, are often observed in individuals with Fetal Alcohol Spectrum Disorders. The neurobiological basis of memory deficits after prenatal alcohol exposure (PAE) is often linked to structural and functional alterations in the medial temporal lobe, including the hippocampus. Recent evidence suggests that the medial temporal lobe plays a critical role in processing high-order sensory stimuli such as complex objects and their associated locations in space. METHODS: In the first experiment, we tested male rat offspring with moderate PAE in a medial temporal-dependent object-place paired-associate (OPPA) task. The OPPA task requires a conditional discrimination between an identical pair of objects presented at two spatial locations 180° opposite arms of a radial arm maze. Food reinforcement is contingent upon selecting the correct object of the pair for a given spatial location. Adult rats were given a total of 10 trials per day over 14 consecutive days of training. PAE male rats made significantly more errors than male saccharin (SACC) control rats during acquisition of the OPPA task. In Experiment 2, rats performed an object-discrimination task in which a pair of objects were presented in a single arm of the maze. Moderate PAE and SACC control rats exhibited comparable performance. The results suggest that moderate PAE rats can learn to discriminate objects, but are impaired when required to discriminate between objects on the basis of spatial location in the environment.